Association of DGAT1 Gene Related to Flavor, Odor, Cholesterol, and Mineral in Indonesian Sheep - Fisma Amri; Ratna Sholatia Harahap; Cece Sumantri; Ismeth Inounu; Depison Depison; Yun Alwi; Asep Gunawan (Indonesian Center for Animal Research and Development (ICARD), 2023)
Diacylglycerol acyltransferase 1 (DGAT1) is a potential candidate gene for improving Indonesian lamb’s quality and nutrient value. The study aimed to identify the diversity of the DGAT1 gene with SNP g.8539 CT and its relation to Indonesian lamb's flavor and odor, cholesterol, and mineral. Total of 254 ten to twelve months old sheep consisted of 20 Javanese fat-tail sheep (JFTS), 107 Javanese thin-tail sheep (JTTS), 10 Garut composite sheep (GCS), 10 Compass agrinak sheep (CAS), 10 Barbados cross sheep (BCS), 20 Garut sheep (GS), 27 Jonggol sheep (JS), and 50 Jambi local sheep (JLS). One hundred sheep were used to analyze the association of the DGAT1 gene with flavor and odor content, cholesterol, and mineral. The diversity of DGAT1|AluI was analyzed with the PCR-RFLP method. The association of the DGAT1 gene with the nutritional value of meat was analyzed using the GLM (General Linear Model) method. The results showed that the DGAT gene was polymorphic in JTTS, GS, and JFTS and monomorphic in CAS, BCS, JLS, and GCS. CC and CT genotypes were found in JTTS, GS, and JFTS. SNP g.8539 CT of DGAT1 gene had a significant association (P0.05) with flavor and odor, 4-Ethyloctanoic Acid (EOA). However, the DGAT1 gene had no significant association (P0.05) with cholesterol and mineral. The DGAT1 gene might be marker-assisted selection for improving lamb flavor and odor in Indonesian sheep.